Axl and MerTK regulate synovial inflammation and are modulated by IL-6 inhibition in rheumatoid arthritis - Alessandra Nerviani; Marie-Astrid Boutet; Giulia Maria Ghirardi; Katriona Goldmann; Elisabetta Sciacca; Felice Rivellese; Elena Pontarini; Edoardo Prediletto; Federico Abatecola; Mattia Caliste; Sara Pagani; Daniele Mauro; et al. (Nature Communications, 2024)
Abstract The TAM tyrosine kinases, Axl and MerTK, play an important role in rheumatoid arthritis (RA). Here, using a unique synovial tissue bioresource of patients with RA matched for disease stage and treatment exposure, we assessed how Axl and MerTK relate to synovial histopathology and disease activity, and their topographical expression and longitudinal modulation by targeted treatments. We show that in treatment-naive patients, high AXL levels are associated with pauci-immune histology and low disease activity and inversely correlate with the expression levels of pro-inflammatory genes. We define the location of Axl/MerTK in rheumatoid synovium using immunohistochemistry/fluorescence and digital spatial profiling and show that Axl is preferentially expressed in the lining layer. Moreover, its ectodomain, released in the synovial fluid, is associated with synovial histopathology. We also show that Toll-like-receptor 4-stimulated synovial fibroblasts from patients with RA modulate MerTK shedding by macrophages. Lastly, Axl/MerTK synovial expression is influenced by disease stage and therapeutic intervention, notably by IL-6 inhibition. These findings suggest that Axl/MerTK are a dynamic axis modulated by synovial cellular features, disease stage and treatment.